2022
DOI: 10.1021/acs.estlett.2c00870
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Exposure to Plastic Additives and Associations with Placental Function-Related Genes

Abstract: Despite an increasing number of environmental reports on plastic additives, gestational exposure to these chemicals has been poorly characterized. The present work aimed to characterize gestational exposure to a total of 50 broadly used plasticizers and antioxidants in women with fullterm (n = 155) and preterm deliveries (n = 75) and to explore the associations of prenatal exposure with the expressions of placental functionrelated genes. A few of them exhibited significantly different concentrations between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…The LLE-based methodologies generally work for both plasma and serum analysis. , For example, Jamnik et al developed an LC-MS assay to determine >80 highly diverse xenobiotics in various human fluids, in which the same LLE-based sample preparation method was employed for plasma and serum . Furthermore, our protocol has already been validated to be applicable for the analysis of OPEs, PAE metabolites, and synthetic antioxidants in serum. , Therefore, we infer that our protocol would be equally applicable for both plasma and serum. Overall, the above-mentioned advantages, along with satisfactory analytical accuracy, precision, and sensitivity, enable our target exposome protocol a promising approach with great potentials for large-scale biomonitoring and epidemiological studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The LLE-based methodologies generally work for both plasma and serum analysis. , For example, Jamnik et al developed an LC-MS assay to determine >80 highly diverse xenobiotics in various human fluids, in which the same LLE-based sample preparation method was employed for plasma and serum . Furthermore, our protocol has already been validated to be applicable for the analysis of OPEs, PAE metabolites, and synthetic antioxidants in serum. , Therefore, we infer that our protocol would be equally applicable for both plasma and serum. Overall, the above-mentioned advantages, along with satisfactory analytical accuracy, precision, and sensitivity, enable our target exposome protocol a promising approach with great potentials for large-scale biomonitoring and epidemiological studies.…”
Section: Discussionsupporting
confidence: 92%
“…29 Furthermore, our protocol has already been validated to be applicable for the analysis of OPEs, PAE metabolites, and synthetic antioxidants in serum. 34,35 Therefore, we infer that our protocol would be equally applicable for both plasma and serum. Overall, the above-mentioned advantages, along with satisfactory analytical accuracy, precision, and sensitivity, enable our target exposome protocol a promising approach with great potentials for large-scale biomonitoring and epidemiological studies.…”
Section: ■ Discussionmentioning
confidence: 98%
“…8,13,14 DPG has been found to occur in human urine with a detection frequency of 73% in children, 15 while N-(1,3-dimethylbutyl)-N′-phenyl-1,4-benzenediamine (6PPD) has also been found to occur in different human samples. 16,17 While some studies that have highlighted the occurrence in wastewater and drinking water systems of compounds like DPG and 6PPD implicate tire wear related sources, 8,18,19 their diverse usage might suggest that others sources play a critical and little studied role in their occurrence in drinking water. 20 The transformation of such compounds in the environment and engineered systems has also been shown to play a major role in toxicity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The occurrence of polymer additives in the environment from surface runoff has been recently associated with serious effects for fish populations, , and while many emerging contaminants are usually found at low nanogram per liter quantities in the environment, numerous recent reports have indicated that polymer additives can occur at much higher concentrations in the microgram per liter range. 1,3-Diphenylguanidine (DPG) has been shown to be a compound having among the highest detected concentrations in different studies of urban runoff waters. , However, DPG occurrence is not restricted to the aquatic environment but has also been reported in urban air, indoor household dust, and drinking water samples. ,, DPG has been found to occur in human urine with a detection frequency of 73% in children, while N -(1,3-dimethylbutyl)- N ′-phenyl-1,4-benzenediamine (6PPD) has also been found to occur in different human samples. , While some studies that have highlighted the occurrence in wastewater and drinking water systems of compounds like DPG and 6PPD implicate tire wear related sources, ,, their diverse usage might suggest that others sources play a critical and little studied role in their occurrence in drinking water . The transformation of such compounds in the environment and engineered systems has also been shown to play a major role in toxicity. , Indeed, we have previously demonstrated that selected chlorinated products of DPG show greater toxicity than the original parent compound while also being potentially genotoxic .…”
Section: Introductionmentioning
confidence: 99%